2002
DOI: 10.1016/s0008-6363(02)00267-5
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolemmal hydraulic conductivity of guinea-pig and rat ventricular myocytes

Abstract: Although the observed L(p) is relatively small in magnitude, the low E(a) and the sulfhydryl reagent-induced modification of L(p) are characteristic of channel-mediated water transport. These data suggest that water flux across the sarcolemma of guinea-pig and rat heart cells occurs through parallel pathways, i.e., the majority passing through water channels and the remainder penetrating the lipid bilayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…The AQP-1-dependent percentage of myocardial water permeability of between 20 and 30%, seen in membranes from knockout mice as well as from wild-type mice treated with HgCl 2 , is consistent with the estimated contribution of AQPs to total myocardial water flux determined by Kellen et al (14,15) in whole heart experiments, although less than that estimated from isolated cardiomyocytes in studies by Ogura et al (36,37). Importantly, water permeability assessed by Kellen et al (14,15) is the net effect of endothelium-and cardiomyocytederived AQPs, whereas that in isolated cells used by Ogura et al (36,37) would include only cardiomyocyte-derived AQPs. It is acknowledged that the three different models discussed above are not strictly comparable.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The AQP-1-dependent percentage of myocardial water permeability of between 20 and 30%, seen in membranes from knockout mice as well as from wild-type mice treated with HgCl 2 , is consistent with the estimated contribution of AQPs to total myocardial water flux determined by Kellen et al (14,15) in whole heart experiments, although less than that estimated from isolated cardiomyocytes in studies by Ogura et al (36,37). Importantly, water permeability assessed by Kellen et al (14,15) is the net effect of endothelium-and cardiomyocytederived AQPs, whereas that in isolated cells used by Ogura et al (36,37) would include only cardiomyocyte-derived AQPs. It is acknowledged that the three different models discussed above are not strictly comparable.…”
Section: Discussionsupporting
confidence: 88%
“…Both structures can be considered as sarcolemmal, either the invaginations of the cell membrane into the Z line in the case of the t-tubules or the pinched-off vesicles in the case of caveolae. AQPs appear to be present in isolated cardiac myocytes as demonstrated by measurement of sarcolemmal permeability (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, water may be conveyed by other cardiac water pores in the absence of AQP4. We have presented evidence for the expression of AQP1 in human cardiomyocytes [55] and a mercury-sensitive form of water transport in rat cardiomyocytes may similarly be explained by the presence of AQP1 [62], also shown by immunofluorescent microscopy [54]. Neither knockout [63] nor overexpression [64] of AQP4 results in altered gross morphology of the mouse heart.…”
Section: Aquaporins In the Heartmentioning
confidence: 69%
“…However, the underlying pathophysiological mechanism of myocardial edema after severe burns has not been fully understood. Recent studies suggested that aquaporins (AQPs), which are crucial for regulation of cell volume, transepithelial water transport, and whole body homeostasis, may play a potential role in cardiac edema (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%